Transformasi Digital UMKM Berbasis Studi Kelayakan Bisnis: Strategi Pemasaran Digital, Sistem Pembayaran QRIS, dan Peningkatan Visibilitas pada Eka Snack - Dellia Mila Vernia; Farida Frihatini; Hugo Aries Suprapto; Febby Anggraini; Bakhrul Ulum; Kayla Tria Hapsari; Diska Multi Sari; Novia Aninda Wardana (Jurnal Pengabdian Masyarakat Nusantara, 2026)
The development of digital technology requires MSMEs to transform in order to remain competitive. Eka Snack, a small snack food enterprise, faces three main challenges: suboptimal digital marketing, a manual cash-based transaction system, and low business visibility on digital platforms. This mentoring program aims to drive Eka Snack's digital transformation through a comprehensive business feasibility study approach. Implementation methods consist of four stages: preparation, execution, mentoring and evaluation, and follow-up. Solutions applied include marketing optimization via Instagram, TikTok, Shopee, and Tokopedia; implementation of a QRIS-based digital payment system; and improved business visibility through Google Maps. Results demonstrate increased marketing reach, transaction efficiency, and digital visibility for Eka Snack. Business owners also gained improved digital literacy supporting more professional and sustainable business management. This program contributes to the achievement of the Sustainable Development Goals (SDGs), specifically Goal 8 (Decent Work and Economic Growth) and Goal 9 (Industry, Innovation, and Infrastructure).